Information System Strategic Planning In PT. Hostingan Awan Indonesia Using Ward & Peppard Methodology - Deni Ekel Ramanda Sembiring Pelawi; Agustinus Fritz Wijaya (Journal of Information System and Informatics, 2020)
Information Systems at this time is needed by the company to survive in business competition with competitors. The information system must also be aligned with the vision and mission and business processes that exist in the company now days so company can generate profits (profitable) at the same time. PT. Hostingan Awan Indonesia is a web development product & service provider company with online transaction feature and purchase processes that integrated with mobile payments. To make business process run optimally, an information system is needed to archive every output document that produced by each division in the company. The process of collecting data in this paper through observation and direct interviews with several stakeholders in the company. This research used Ward & Peppard metho with internal value chain analysis, SWOT, PEST, Five Forces Porter and Mc Farlan Strategic Grid. This research also provides application portfolio recommendations with internal business environment analysis, external business environment analysis, internal SI environmental analysis and external SI environmental analysis.